Polychromatic emission from polar-plane-free faceted InGaN quantum wells with high radiative recombination probabilities. (19th June 2017) - Matsuda, Yoshinobu; Funato, Mitsuru; Kawakami, Yoichi
Abstract: We fabricated three-dimensional (3D) InGaN quantum wells (QWs) on semipolar GaN substrates by selective area epitaxy. It was found that polar-plane-free 3D structures can be fabricated with a particular mask pattern on the plane and that InGaN/GaN QWs on these structures exhibit facet-dependent polychromatic emission properties. In addition, time-resolved photoluminescence spectroscopy indicated that the radiative recombination lifetimes of the obtained 3D QWs without the polar (0001) plane are much shorter than those of conventional 3D QWs with the (0001) plane, particularly at long wavelengths.